Perpetuating Victimization with Efforts to Reduce Human Trafficking: A Call to Action for Massage Therapist Protection - Rosenow, Mica; Munk, Niki (International Journal of Therapeutic Massage & Bodywork, 2023)
Human trafficking guised as massage therapy businesses is a highly successful business model that creates independent but related victims beyond the women and girls forced into sex work. Massage clinicians and the massage therapy profession are also negatively impacted by the trafficking massage business model with over 9,000 established illicit massage businesses marketing services alongside professional therapeutic massage businesses. Credential regulation efforts advocated for by various massage-related professional organizations and regulat-ing agencies have fallen short in their purported intentions to protect massage therapists and trafficking victims. Massage industry advocates continue endorsing massage therapy as a branch of health care although healthcare workers are not generally considered or treated as sex workers. Sexual harassment research in direct patient care disciplines, such as physical therapy and nursing, points to a high patient initiated incident rate and transdisciplinary, detrimental mental health outcomes for clinicians. Reporting and debriefing instances of sexual harassment inside of healthcare organizations, covered by The Civil Rights Act of 1964, promotes a victim-centered perspective to support the well-being of past, current, and pending victims. The massage therapy workforce is comprised of mainly female sole proprietors, creating a double vulnerability in their potential to experience sexual harassment. This threat is compounded by little-to-no protective or supporting systems or networks for massage clinicians. The priorities of professional massage organizations to depend on credentialing and licensing as their primary efforts to fight human trafficking, seems more to perpetuate the current system/expectations, leaving individual massage therapists responsible for fighting or reeducation deviant sexualized behaviors. This critical commentary closes with a call to action aimed at professional massage organizations, regulators, and corporations to protect massage therapists through a unified position, supported in word, policy, and action, against sexual harassment, and unequivocally condemns professional massage devaluation and sexualization in all forms.